STUDY AND FABRICATION OF COMPRESSED AIR ENGINE - Sharma, Ruby; Singla, Naveen (IJRDO -Journal of Computer Science Engineering, 2015)
As we all know the world is hard pressed with the prices and crises of energy and fuel, and is also then compounded by pollution of all kinds, so we need an early solution to overcome this problem of fuel crises (which also further leads to fuel price hikes ) and also the major problem of pollution , so any technologies that bring out the solutions to this problem is considered as a bounty. One of the solution to this huge problem in such new technologies, is the development of a new engine called as compressed air engine which does not require any of the fuels like Diesel, Petrol, CNG, LPG, Hydrogen etc. this works using only compressed air so it completely overcomes the problem of Pollution so also its exhaust is clean and cool measured practically as low as 5ºC. A proto type, a horizontal, single cylinder low speed engine was modified to run on compressed air. Since this engine runs only on high pressure compressed air, the exhaust of which is undoubtedly only air, making it a zero pollution engine. No heat is generated because there is no combustion of fuel, hence this engine needs no cooling system and it result in reduced cost, weight, volume and vibration. Also it’s very cost effective and the operational cost is ten times less than that of petrol or diesel. Experimental analysis were carried out on this modfied engine to find out its performance characteristics like brake power, mechanical efficiency, overall efficiency, air to Air ratio, volumetric efficiency, cost analysis etc. Though the efficiencies were low as the frictional forces were high for the proto designed engine, however this concept can be carried out on a professionally designed engine to improve its performance and stability.